MODULATION PROCEDURE ON TABOO IN ME AND EARL AND THE DYING GIRL - Farros Bayu Panuntun (PARADIGM: Journal of Language and Literary Studies, 2023)
This study discusses the translation procedure of taboo words and the acceptability aspects of translation in the Indonesian translation novel Me and Earl and the Dying Girl. This study applied a descriptive-qualitative approach using Vinay Darbelnet’s modulation theory and Nababan’s acceptability concept. As a result, 92 translation procedures of unfindable words, 30 fixed modulations, and 62 free modulations were found. Those 92 taboo words were classified into Jay’s classification of taboo terms, which consisted of 22 data on sexual reference, 11 data on profane, 7 data on scatological referents, 7 data on animal names, 10 data on ethnic-racial-gender slurs, 4 data on insulting references, 5 data on ancestral allusions, 2 data on substandard vulgar items, and 24 data on offensive slang. For the acceptability analysis, this study took eighteen samples from Jay's nine types of taboo terms to be rated by the respondents. The respondents were final-year English Literature Department students of UIN Syarif Hidayatullah Jakarta. The results showed that the translation results tended to be acceptable.